The Relation of Social Studies Learning with Flood Response Attitudes Students of Walisongo Junior High School in Pecangaan Jepara in 2017/2018 - Zahara, Izzah; Rusdarti, Rusdarti; Banowati, Eva (JESS (Journal of Educational Social Studies), 2018)
Social studies learning aims to enable students to solve the social problems they face and make as good citizens. Walisongo Junior High School is a school where most of the students live in flood-prone areas, so that students’ home affect their caring attitude towards their environment. The purpose of this study is to analyze the relationship of social studies learning to the flood caring attitude of students at Walisongo Junior High School. The method used in this research is qualitative method. The technique of collecting data is in-depth interviews, observation and document study. The results showed that students’ caring attitude towards the environment at Walisongo Junior High School was still low. Social studies learning that is still monotonous has a direct impact on students’ caring attitude towards the environment. This research is expected to be able to provide solutions to increase the concerning of environment particularly.